2007
DOI: 10.1111/j.2007.0030-1299.15683.x
|View full text |Cite
|
Sign up to set email alerts
|

The complementarity of single-species and ecosystem-oriented research in conservation research

Abstract: There has been much debate about the relative merits of single-species vs ecosystem-oriented research for conservation. This debate has become increasingly important in recent times as resource managers and policy makers in some jurisdictions focus on ecosystem-level problems. We highlight the potential strengths and limitations of both kinds of research, discuss their complementarity and highlight problems that may arise where competition occurs between the two kinds of research.While a combination of approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…An ongoing debate in conservation is the relative merits of single‐species versus ecosystem‐oriented conservation (Lindenmayer et al ., ). Bowen () saw this as a divergence between systematists, supporting the importance of phylogeny, ecologists arguing for the protection of populations or ecosystems, and evolutionary biologists promoting the factors that enhance adaptation and biodiversity, and proposed that it could be resolved if conservation efforts are directed towards preserving processes of life.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An ongoing debate in conservation is the relative merits of single‐species versus ecosystem‐oriented conservation (Lindenmayer et al ., ). Bowen () saw this as a divergence between systematists, supporting the importance of phylogeny, ecologists arguing for the protection of populations or ecosystems, and evolutionary biologists promoting the factors that enhance adaptation and biodiversity, and proposed that it could be resolved if conservation efforts are directed towards preserving processes of life.…”
Section: Discussionmentioning
confidence: 97%
“…Lindenmayer et al . () argue for an approach that targets limited resources for conservation research at projects that may close important knowledge gaps, while also promoting ongoing synergies between single‐species and ecosystem‐oriented research. We concur and agree with Caro & Laurenson () that this process needs to be studied over a wider selection of landscapes in order to better understand diversity of intra‐ and interspecific community dynamics and ecosystem function, and to promote the conservation of all facets; compositional, structural and functional, of biodiversity (Noss, ).…”
Section: Discussionmentioning
confidence: 99%
“…no E. armatus seen after a ‘blackwater’ event), with a general view that their fresh waters are ‘unhealthy’ without this key species. Although there is some debate over single‐species conservation being abandoned in favour of ecosystem‐based approaches (Franklin, ; Lindenmayer et al, ), a flagship species that carries strong social values could be pivotal in engaging and maintaining long‐term stakeholder participation in conservation initiatives. In the case of a long‐lived species like E. armatus (living up to 28 years), with a small home range (Gilligan et al, ; Ryan, Ebner, & Norris, ), there is huge potential for the broader communities to develop deep connections with local populations, via long‐term monitoring in citizen‐science programmes or local habitat restoration projects, which allows participants to see and to help adapt conservation efforts in their region (Bonney et al, ; Dickinson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One final aspect of lake monitoring that deserves mention is that the CEN standards for lake hydromorphology are directed at habitat features and processes. Maintaining or restoring natural processes within lakes and rivers is generally accepted as a foundation of freshwater conservation, but the extent to which species monitoring should also be part of an overall monitoring programme is the subject of debate (Lindenmayer et al, ). Some have suggested that species conservation is more appropriately achieved by focusing on conserving habitats and ecological processes than by considering the needs of individual species.…”
Section: Applications Of the Cen Standardsmentioning
confidence: 99%